1989
DOI: 10.1136/jnnp.52.6.742
|View full text |Cite
|
Sign up to set email alerts
|

Reaction time after head injury: fatigue, divided and focused attention, and consistency of performance.

Abstract: SUMMARY Three groups of patients who had suffered head injury were compared with matched control subjects on reaction time (RT) tasks. Group I consisted of outpatients previously hospitalised for head injury ofwide ranging degrees of severity, assessed at varying intervals after injury. Group II was composed of non-hospitalised mildly concussed patients. Group III was made up of head injured patients of varying degrees of severity assessed 7-10 months after initial hospitalisation for their injury. The reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
249
2
5

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(271 citation statements)
references
References 12 publications
(2 reference statements)
15
249
2
5
Order By: Relevance
“…The finding that mild TBI participants showed deficits in selective and sustained attention is consistent with a number of studies that have reported problems with attention (e.g., Gentilini et al, 1985Gentilini et al, , 1989Mclean et al, 1983;Stuss et al, 1989). The poorer verbal memory of the mild TBI group also confirms the findings of previous studies undertaken with mild TBI patients (e.g., Dikmen et al, 1986;Stuss et al, 1985).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The finding that mild TBI participants showed deficits in selective and sustained attention is consistent with a number of studies that have reported problems with attention (e.g., Gentilini et al, 1985Gentilini et al, , 1989Mclean et al, 1983;Stuss et al, 1989). The poorer verbal memory of the mild TBI group also confirms the findings of previous studies undertaken with mild TBI patients (e.g., Dikmen et al, 1986;Stuss et al, 1985).…”
Section: Discussionsupporting
confidence: 82%
“…Deficits in selective and sustained attention have also been demonstrated following mild TBI (Bigler & Snyder, 1995;Gentilini et al, 1989;Mclean et al, 1983;Stuss et al, 1989). However, studies of executive functioning have reported inconsistent findings.…”
Section: Introductionmentioning
confidence: 89%
“…The serial reaction time task is negatively affected by fatigue. 8,18 The three reaction time tests used in this study were administered using a computer-based program designed using MEL Professional version 2.0 software (Psychology Software Tools, Inc., Pittsburgh, Pennsylvania). For the simple reaction time test, the subject was instructed to strike a key as quickly as possible when a particular number appeared on the screen.…”
Section: Methodsmentioning
confidence: 99%
“…The following additional categories were formed to accommodate the other tests of attention: (a) working memory, which shares important similarities with attention (Baddeley, 1993b; Digit Span backwards from the WAIS-R and Paced Auditory Serial Addition Test [PASAT; Gronwall, 1977]); (b) Picture Completion (WAIS-R subtest), which may assess attention to visual detail (Gray et al, 1992); (c) Mental Control (Wechsler Memory ScaleRevised subtest;Wechsler, 1987); (d) simple reaction time (RT); (e) choice RT, which may measure aspects of attention (e.g., Stuss et al, 1989;Van Zomeren & Brouwer, 1994; but also see Ponsford & Kinsella, 1992); and (f) other, which included infrequently used measures (e.g., divided attention and time estimation). A few direct-retraining studies also measured participant-reported mood with depression or anxiety inventories, as well as subjective ratings of attention on a particular task by participants, other observers, or both.…”
Section: Variables Coded From Studiesmentioning
confidence: 99%